Соціальне виключення: проблеми визначення та дослідження - Рєвнівцева, О.В. (Інститут демографії та соціальних досліджень НАН України, 2008)
В статье изучена история возникновения и распространения категории «социальное исключение», выяснены содержание данного понятия и подходы к его определению, проанализирована возможность использования концепции социальной эксклюзии в условия Украины. This article sheds light on the history of the origin and spreading of the “social exclusion” category. It also outlines the essence of this notion and the approaches to its definition, and analyzes the possibility of the usage of the social exclusion conception in Ukraine.